2015
DOI: 10.36366/frontiers.v26i1.351
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Preference for the Exported Campus Model of Study Abroad

Abstract: There is considerable debate in the study abroad community about the efficacy of exported campus or “island” programs in which students and faculty are transported from their home campus to a largely self-contained community within the host culture. One uninvestigated aspect of this issue is the degree to which there are pre-existing differences between students who prefer such programs and those attracted to more immersive experiences. This study used discriminant analysis of data from a questionnaire adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…Their study showed potential applications for SEIC in a sample of professionals with overseas sojourning and teaching experience. However, the original scale development attempt used a relatively modest sample size (N = 213) of former sojourning teachers and ended with preliminary checks for internal validity, likely contributing to some hesitancy to select or adopt the instrument in related assessment research (Goldstein, 2015). This report offers numerous positions in favor of the approach and instrument taken by Peterson et al (2011) with further theoretical support due to the usefulness of an SEIC construct in applied settings and addresses questions of validity to evaluate its potential as a tool for evaluators and educators.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study showed potential applications for SEIC in a sample of professionals with overseas sojourning and teaching experience. However, the original scale development attempt used a relatively modest sample size (N = 213) of former sojourning teachers and ended with preliminary checks for internal validity, likely contributing to some hesitancy to select or adopt the instrument in related assessment research (Goldstein, 2015). This report offers numerous positions in favor of the approach and instrument taken by Peterson et al (2011) with further theoretical support due to the usefulness of an SEIC construct in applied settings and addresses questions of validity to evaluate its potential as a tool for evaluators and educators.…”
Section: Introductionmentioning
confidence: 99%
“… Mak and Tran (2001) assigned direct applications of self-efficacy to language and intercultural competence according to the criteria put forth by Bandura ( Li and Gasser, 2005 ), such that domain-specific self-efficacy for language learners involves engaging actively in controlled cross-cultural interactions of social significance, observing peers perform in these interactions, seeking constructive feedback, and overcoming emotional arousal to enhance performance. Self-efficacy has also been tagged as a factor influencing sojourner and intercultural adjustment ( Hechanova-Alampay et al, 2002 ) for both domestic and international sojourners ( Goldstein, 2015 ). In a meta-analysis reporting a moderate effect size, cross-cultural self-efficacy change from intercultural adjustment was observed longitudinally and opposed measures of anxiety ( Wilson et al, 2013 ), indicating its crosscutting role as a situational factor in these applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive attitude toward language learning is predictive of interest in study abroad (Goldstein & Kim, 2006) and preference for a more immersive study abroad experience (Goldstein, 2015). Furthermore, proficiency in one's host culture language is associated with a number of positive study abroad outcomes, including early sociocultural adaptation and higher levels of psychological well-being (Savicki, 2011).…”
Section: Second Language Acquisitionmentioning
confidence: 99%
“…Changes in personal, ethnic/racial, and national identity are a common outcome of study abroad (Savicki & Cooley, 2011), yet students may fail to anticipate these changes (Goldstein & Keller, 2015). Psychology instructors can assist students in understanding the concept of identity and exploring potential changes in self-concept that may result from their study abroad experience.…”
Section: Relevant Psychological Conceptsmentioning
confidence: 99%